Personal and social factors related to the beginning of sexual activity in students of an educational institution (Lima, Perú) [Factores personales y sociales relacionados con el inicio de la actividad sexual en estudiantes de una institución educativa (Lima, Perú)] - Apaza-Guzmán, Lissette Consuelo (2018)
ABSTRACT Objective: To identify the personal and social factors related to the beginning of sexual coital activity in students of an Educational Institution. Methodology: Research with observational design, correlation level and cross section. The study involved 136 students from 3rd to 5th year of high school, randomly selected in the month of October 2016. An instrument developed by the authors was applied and validated by expert judgment. The statistical test was χ2, considering as significant a value p <0.05. Results: It can be seen that 27.2% of the students surveyed reported having had sexual intercourse. The personal factors with significant association were: having more than three lovers (p= 0.004), the adolescent’s permissiveness to sexual relations (p= 0.001), the valuation towards sexual relations (p= 0.021), and having repeated or once disapproved the school year (p= 0.000). In the case of social factors, attending fashion parties (p = 0.000) and having consumed some type of alcoholic beverage (p= 0.003) were significant. Conclusion: Personal and social factors are associated with the beginning of sexual activity of adolescents, especially those that predispose them to adopt risky behaviors, or that favor sexual experiences with their partners or close friends.